2016
DOI: 10.1021/acs.jpcc.6b00865
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy Ordering and Electron Localization in CeO2: Hybrid Functional Study

Abstract: Oxygen vacancies in bulk CeO 2 have been investigated using the Heyd−Scuseria−Ernzerhof (HSE) hybrid functional method. Results show that oxygen vacancies tend to linearly order in the ⟨111⟩ direction of CeO 2 , yielding much more dispersive gap states with the weakened electron localization compared to the case of a single vacancy. Such vacancy ordering and electron localization give rise to a profound influence on material properties. First, the dispersive gap states are expected to act as stepping stones to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 69 publications
(67 reference statements)
4
37
0
Order By: Relevance
“…Nano-ceria has already been widely used as a component of various catalysts, protective corrosion-resistant coatings for metals and alloys, polishing mixtures and abrasives 1-3, 12, 13 . It is anticipated that the production of engineered ceriabased nanomaterials will notably increase in the immediate future, because of emerging ceria applications in UV filters 4,5,14 , solid oxide fuel cells 6,7,[14][15][16][17][18] and pharmacology [8][9][10][11] . Rapidly growing demand in ceria-based materials inevitably results in their release to the environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-ceria has already been widely used as a component of various catalysts, protective corrosion-resistant coatings for metals and alloys, polishing mixtures and abrasives 1-3, 12, 13 . It is anticipated that the production of engineered ceriabased nanomaterials will notably increase in the immediate future, because of emerging ceria applications in UV filters 4,5,14 , solid oxide fuel cells 6,7,[14][15][16][17][18] and pharmacology [8][9][10][11] . Rapidly growing demand in ceria-based materials inevitably results in their release to the environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies focused on vacancy-vacancy interactions, but did not explore the single vacancy in CeO 2 [53].…”
Section: Introductionmentioning
confidence: 99%
“…The higher ability of GBs to adsorb/trap the impurities (here vacancies) than the free surfaces was reported by others [47]. The ferromagnetism generated by defects such as oxygen vacancies at free surfaces of oxides is frequently reported [8,14,18]. However, the total solubility of impurity elements (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Nevertheless, there are studies which have demonstrated that a high concentration of oxygen vacancies and/or high density of states associated with these defects can induce RTFM in undoped CeO 2 [8,14,18]. Singhal et.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation